Chylothorax due to Mycobacterium tuberculosis. Issue 9 (September 1995) - Antón, P A; Rubio, J; Casán, P; Franquet, T
Abstract : Chylothorax in an adult is a rare cause of pleural effusion. Mycobacterium tuberculosis may cause chylous effusion, but usually in association with extensive intrapulmonary involvement. A case of chylothorax is presented in which M tuberculosis was isolated from the pleural fluid and was the only intrathoracic manifestation of tuberculosis.